Absence of social conditioned place preference in BTBR T+tf/J mice: relevance for social motivation testing in rodent models of autism - Pearson, Brandon L. (2012)
A major goal of translation research in autism is to characterize the physiological and psychological processes underlying behavioral abnormalities. Since autism reflects impairments in social motivation, we modified the mouse three-chamber social approach apparatus for use as a social conditioned place preference arena. We paired one of two unique contexts with social interactions in juvenile mice for five or ten conditioning sessions in BTBR T+tf/J mice and a control strain with normal approach behaviors (C57BL/6J) since the BTBR T+tf/J inbred mouse strain displays a variety of behavioral alterations analogous to symptoms of autism spectrum disorders. While C57BL/6J mice formed a conditioned place preference to the context associated with social interactions, particularly those receiving ten days of conditioning, BTBR T+tf/J mice did not. Neither absence of social proximity nor avoidance due to high rates of autogrooming appeared to underlie the impaired positive incentive value of the unconditioned social stimulus in the BTBR T+tf/J strain. These data contribute to a growing body of evidence suggesting that the BTBR T+tf/J strain shows impairments in all diagnostic domains of autism including social motivation. Additionally, social conditioning testing might provide an important social motivation measure in other rodent models of neuropsychiatric disorders characterized by social abnormalities.